Строительство и реконструкция угольных шахт - Баронский И. В. Исаак Владимирович; Ерофеев Л. М. Леонид Михайлович; Умнов Н. Р. Николай Романович; Каравайцев М. Г. (Москва, Недра, 1983)
Авт. указаны на обороте тит. л.